Urban innovation and autonomy - "Clarke, Susan E (ed.)" (New Delhi, 1989)
This paper is an attempt to explain the dynamics of the new politics in Japan by examining changes in local politics, the harbinger of national political changes. The theoretical position of this paper is based on the new political culture (NPC) perspective. The NPC perspective focuses on the changing political attitudes and actions of the public and the political elite in many advanced societies. From the NPC perspective, this paper examines the NPC policy preferences of the Japanese local mayors, which include populism, efficient fiscal spending, decentralization and anticlientelistic politics. The influence of the NPC on the policy changes in the local governments is also examined. By examining the decline of clientelistic fiscal spending in the cites with NPC demographic characteristics, this paper shows the dynamic of the NPC in the local policy outputs.
Keywords: Urban Policy